Precalibrated Ion Beam Identification Detector - Collet, Philippe Klintefelt; Lundmark, Rikard (My University, 2012)
When conducting experiments with radioactive beams, a recurring problem is to iden- tify the ions occurring in the beam. The identification process makes use of different detectors, which must be calibrated prior to usage — a process often requiring beam. This project investigates a concept and design for a help detector that can be calibrated without beam access. This pre-calibrated detector is to be used at the initial calibration of other detectors in the experimental setup, in order to save expensive beam time. The calibration in question is performed by, in turn, making absolute identifications of indi- vidual ions that have been detected by the main experimental setup. This identification is done by utilizing coincidence between β- and γ-decays in the detector and comparing measured γ-energies with tabulated values. The detector was simulated using the Geant4 toolkit, and the γ-energies were re- trieved from the ENSDF database. It was found that using sufficiently low beam inten- sities, the detector could successfully identify most of the 17C ions in a beam composed of several different nuclides with mass and charge in the vicinity of those of 17C. The time of the identification was 13 hours, which is about one order of magnitude too long compared to what would be desirable in real-world experiments. Whether it is possi- ble to further improve the design, and thereby increase the efficiency, will have to be concluded by further studies.
Keywords: Grundläggande vetenskaper; Lågenergifysik; Basic Sciences; Low energy physics